Are there any unwanted anesthesia symptoms in patients undergoing anesthesia? - Dominika Malczyk; Katarzyna Marczak; Agata Miśtal; Klaudia Solga; Adriana Milena Borodzicz; Sylwia Anna Krzemińska (Kazimierz Wielki University, 2018)
Introduction. General anesthesia deprives the patient of consciousness and the abolition of sensation and reflexes. Undesirable post-anesthesia symptoms after surgery may affect all patient's body systems. Aim. The aim of the study was to assess the occurrence of undesirable symptoms of anesthesia in patients undergoing general and regional anesthesia. Materials and methods. The study included 91 patients: 46 women and 45 men from different surgical wards. The method used in the work was the questionnaire interview. Conclusions. The most frequently occurring post-operative symptom after anesthesia is pain in the surgical area. There is no dependence between the occurrence of undesirable side effects after general and ductal anesthesia and age. There is a dependence between the occurrence of adverse effects and sex. The most frequently performed anesthesia in the examined group of patients was general anesthesia and it carried more undesirable anti-anesthesia symptoms. There is a need for a deeper analysis of the causes of post-anesthesia side effects.